Association of greater intravenous volume infusion with shorter hospitalization for patients with post‐ERCP pancreatitis. Issue 6 (June 2014) - Sagi, Sashidhar V; Schmidt, Suzette; Fogel, Evan; Lehman, Glen A; McHenry, Lee; Sherman, Stuart; Watkins, James; Coté, Gregory A
Abstract Background and Aim There are no data specifically correlating early intravenous volume infusion (IVI) with the length of hospitalization for postendoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP). Methods We conducted a retrospective cohort study of patients admitted within 24 h after ERCP to our institute with PEP. IVI during the first 24 h after ERCP was assessed. Primary outcome was severity of PEP, defined by length of hospitalization according to consensus guidelines: mild ≤ 3, moderate 4–10, and severe > 10 days. Results Of 72 eligible patients, 41 (56.9%) had mild and 31 (43.1%) moderate/severe PEP. Both groups had comparable demographics, indications, and procedural factors except patients with moderate/severe PEP were older (median age 49 vs 36 years, P = 0.05) and more likely to be discharged and readmitted within the first 24 h (41.9% vs 14.6%, P < 0.01). Patients with mild PEP received significantly greater IVI during the first 24 h (2834 mL [2046, 3570] vs 2044 mL [1227, 2875], P < 0.02) and 50% more fluid post‐ERCP (2270 mL [1435, 2961] vs 1515 [950–2350], P < 0.02) compared with those with at least moderate PEP. Conclusion In patients with PEP, greater IVI during the first 24 h after ERCP is associated with reduced length of hospitalization. Lower IVI was more commonly observed in individuals who were discharged and then readmitted during the first 24 h.